2009
DOI: 10.1111/j.1600-0404.2009.01265.x
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythm of stroke onset during the month of Ramadan

Abstract: A significant shift of the circadian pattern of stroke onset time from the period between 6:00 a.m. and noon to that between noon and 6:00 pm has been found during the month of Ramadan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Most of the previous studies compared heterogeneous groups of patients (both ischemic stroke and intracerebral hemorrhage),20 and did not include a non‐fasting group at the time of Ramadan 19, 21, 22…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the previous studies compared heterogeneous groups of patients (both ischemic stroke and intracerebral hemorrhage),20 and did not include a non‐fasting group at the time of Ramadan 19, 21, 22…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors include medical conditions (hypertension, diabetes mellitus, dyslipidemia, atrial fibrillation, sleep apnea, and others), lifestyle (smoking, physical activity)12, 13 and environmental factors (air temperature and air pollution14, 15, 16, 17, 18). Ramadan associated changes such as poor drug therapy compliance; reduced glycemic control, and dehydration may temporarily contribute to stroke risk, yet such an increased stroke risk during Ramadan has not been reported 19, 20, 21, 22…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This study confirmed the findings from previous studies that the higher frequency of stroke onset time was from 6:00 AM to noon one month before Ramadan, whereas contrary to the previous studies, the frequency was higher from noon to 6:00 PM during Ramadan. They concluded that when fasting, the changes in food intake or sleep timings, affect the circadian rhythm and influence the onset time of acute coronary events (43).…”
Section: Discussionmentioning
confidence: 99%
“…Circadian periodicity in the onset of cerebrovascular events has been reported with a predominantly morning surge during the diurnal variability (1)(2)(3). But the effects of the periodicity on acute outcome have not been adequately addressed.…”
Section: Introductionmentioning
confidence: 99%